Prevalence and Factors Associated With Depression and Suicidal Ideation During the COVID-19 Pandemic Among University Students in Uganda: A Cross-Sectional Study - Kaggwa, Mark Mohan; Arinaitwe, Innocent; Nduhuura, Elicana; Muwanguzi, Moses; Kajjimu, Jonathan; Kule, Moses; Ajuna, Noble; Machacha, Ivan; Nkola, Rahel; Najjuka, Sarah Maria; Wamala, Nicholas Kisaakye; Bongomin, Felix; et al. (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic has negatively impacted psychosocial well-being and mental health of students across the world. Although students are vulnerable to depression and suicidal ideation, few studies have been conducted in Uganda. This study aimed to determine the prevalence of depression and suicidal ideation, and associated factors among university students in Uganda. Methods: A cross-sectional study was conducted among undergraduates (N = 540; 363 males; mean age = 23.3 [±2.64] years) recruited from four universities using an online questionnaire that explored sociodemographic factors, depression, and other associated factors. The Patient Health Questionnaire (PHQ-9) was used to assess depression, and Item 9 was used to assess suicidal ideation in the past two weeks. Multivariable logistic regression analyses were performed to determine the factors associated with depression and suicidal ideation. Results: The prevalence of moderate to severe depression was 20% (n = 108) (cut-off: 10/27 based on the PHQ-9), and the prevalence of past-two-week suicidal ideation was 13.89% (n = 75) (cut-off: 1/3 based on the PHQ-9 Item 9)). About half of the individuals who screened positive for depression had suicidal ideation. Factors associated with depression were: having relationship issues (adjusted odds ratio [aOR] = 1.79, 95% confidence interval [CI] = 1.13–2.81, p = 0.012), and having a history of sexual abuse (aOR = 2.06, 95% CI = 1.10–3.84, p = 0.023). Factors associated with reducing the risk of depression were satisfaction with current academic performance (aOR = 0.50, 95% CI = 0.32–0.79, p = 0.003), and being in the fifth year of academic study (aOR = 0.16, 95% CI = 0.03–0.73, p = 0.018). Factors associated with suicidal ideation were: smoking cigarettes and/or marijuana (aOR = 4.83, 95% CI = 1.10-21.12, p = 0.037), and having financial tuition constraints (aOR = 1.85, 95% CI = 1.08 – 3.16, p = 0.024), However, satisfaction with current academic performance reduced the likelihood of suicidal ideation. Conclusions: It is recommended that the university authorities implement measures to provide psychological support for the students with problems concerning financial tuition constraints, relationships, and sexual abuse. Also, all students with depression should be screened for suicidality.